PERENCANAAN BAHAN BAKU DAN HASIL PRODUKSI MENGGUNAKAN METODE LINIER PROGRAMMING SIMPLEK - Monika Handayani; Eka Kusuma Dewi (Universitas Bunda Mulia, 2016)
CV. Baja Utama Landasan Ulin is a business entity that manufactures various products using the basic ingredients of iron. In the management of raw materials for the production of common regulatory process raw materials into sections for further processing. This setting is often done manually without doing careful planning, so that at the end of each production process there are many remaining pieces of the raw materials that should be used in production. In addition to the determination of the production is necessary to reference how the product should be made for each type of existing products. This is often an important factor that pushed for the optimization of production planning in determining the number of products for each type of product and raw material consumption.Linear Programming is one of the methods used in production planning to regulate the use of raw materials is limited. Simplex method is part of the linear programming method that can be used in the production planning system implementation. Simplex method identifies an initial basic solution and then move systematically to other basic solution that has the potential to improve the value of the objective function.The calculation result of production planning using the simplex method can be used as a reference in the decision making production planning. By building an application using the simplex method can assist in the calculation of production peencanaan more efficiently and effectively. Accuracy testing system constructed show significant results with great value reached 94% level of accuracy.Keywords: simplex, production planning, the maximum gain, linear programming